Opportunity Finding by Nascent Entrepreneurs: Accidental or Purposeful? - Zhou, Rongji; Wu, Sibin (Frontiers in Psychology, 2021)
Purpose: This research studies an important, but relatively unexplored entrepreneurial aspect: motivation and aspiration on opportunity finding/discovery. Design/methodology/approach: This study surveyed 230 nascent entrepreneurs on their opportunity finding behavior. A poisson regression and a logistic analysis were conducted to discover the relationship between motivation/aspiration and opportunity search behavior. Findings: Motivation and aspiration interact to influence active search in a positive way. However, only willingness to become an entrepreneur is found to search for opportunities purposefully. Research limitations/implications: Participants of the research are from a Midwest state in US. Future research may collect sample from more and larger areas. Practical implications: Bankers may use entrepreneurial opportunity search behavior as one criterion determining if to fund a person or not. Originality/value: The paper answers the call to study motivation/aspiration on opportunity finding (Yitshaki & Kropp 2018). It is one of the first studies to explore the above relationship.